Simulated Workplace Protection Factors for Half-Facepiece Respiratory Protective Devices - Duling, Matthew G.; Lawrence, Robert B.; Slaven, James E.; Coffey, Christopher C. (Journal of occupational and environmental hygiene, 2007)
This study investigates two different methods (random effects model and 5th percentile) for determining the performance of three types of respiratory protective devices (elastomeric N95 respirators, N95 filtering-facepiece respirators, and surgical masks) during a simulated workplace test. This study recalculated the protection level of three types of respiratory protective devices using the random effects model, compared the two methods with each other and the APF of 10 for half-facepiece respirators, and determined the value of each of the fit test protocols in attaining the desired level of simulated workplace protection factor (SWPF). Twenty-five test subjects with varying face sizes tested 15 models of elastomeric N95 respirators, 15 models of N95 filtering-facepiece respirators, and 6 models of surgical masks. Simulated workplace testing was conducted using a TSI PORTACOUNT Plus model 8020 and consisted of a series of seven exercises. Six simulated workplace tests were performed with redonning of the respirator/mask occurring between each test. Each of the six tests produced an SWPF. To determine the level of protection provided by the respiratory protective devices, a 90% lower confidence limit for the simulated workplace protection factor (SWPF LCL90% ) and the 5th percentile of simulated workplace protection factor were computed. The 5th percentile method values could be up to seven times higher than the SWPF LCL90% values. Without fit testing, all half-facepiece N95 respirators had a 5th percentile of 4.6 and an SWPF LCL90% value of 2.7. N95 filtering-facepiece respirators as a class had values of 3.3 and 2.0, respectively, whereas N95 elastomeric respirators had values of 7.3 and 4.6, respectively. Surgical masks did not provide any protection, with values of 1.2 and 1.4, respectively. Passing either the Bitrex, saccharin, or Companion fit test resulted in the respirators providing the expected level of protection with 5th percentiles greater than or equal to 10 except when passing the Bitrex test with N95 filtering-facepiece respirators, which resulted in a 5th percentile of only 7.9. No substantial difference was seen between the three fit tests. All of the SWPF LCL90% values after passing a fit test were less than 10. The random model method provides a more conservative estimate of the protection provided by a respirator because it takes into account both between- and within-wearer variability.